Analysis of Students’ Conceptual Understanding on Colloidal Materials Through the Flipped Classroom Learning Model Integrated Peer-Instruction - Tasya Fatacharmita; Tritiyatma Hadinugrahaningsih; Irwanto Irwanto (Journal of Computers for Science and Mathematics Learning, 2024)
This study aims to obtain an overview of students’ conceptual understanding on colloidal materials by applying the flipped classroom integrated with peer-instruction. The research method used is qualitative method. This research was conducted at SMA Negeri 8 Depok in the even semester of the 2021/2022 academic year. The research subjects were students of class XI IPA 3 which amounted to 39 students. Research data were collected from observation sheets, reflective journals, researcher notes, conceptual understanding sheets, conceptual understanding test, and interviews. In this study, to analyze the categories of students’ conceptual understanding level used categories adapted from Abraham et al. (1992), namely understanding, lack of understanding, misconceptions, not understanding, and no response. Learning was conducted face-to-face used flipped classroom integrated peer-instruction. The flipped classroom integrated peer-instruction learning model consist of three stages, namely pre-class learning, in-class learning, and after-class learning. During in-class learning, students were given a ConcepTest. The percentage of ConcepTest results was 30% - 70% so that learning continued with group discussion. In all colloidal sub-materials, the majority of students were in the “understand” category with an average percentage of 60,17%. The conclusion of this study is that the flipped classroom learning model integrated with peer-instruction can help students develop students’ conceptual understanding of colloidal material. The integrated flipped classroom and peer instruction can be an alternative in learning activities to develop students’ conceptual understanding.